Religion: border agent between the sacred and the profane - Henrique Camargo, Marcos (2023)
This article aims to present characteristics of religions as intermediaries of human relations between the sacred and profane universes. In this sense, it analyzes the evolution of religions, especially Christianity and its theologies linked to Greco-Roman philosophies, especially the neoplatonism of Plotinus. With this, Christianity distances itself from the universe of the sacred to the sphere of the profane, by neglecting relations with the sacred, to devote itself to the discipline of the body of the Christian in the profane world.